STUDI KOMPARASI EKONOMI ISLAM DI NEGARA KAMBOJA DENGAN NEGARA INDONESIA - Fariz Hafizh Zulfi Barus, Fariz; Rahmayati (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze and compare the development of Islamic economics in Indonesia and Cambodia. The research will focus on the policies, challenges, and potential of each country. As a system based on Sharia principles, Islamic economics offers a fair, ethical, and sustainable alternative to conventional economic systems. Indonesia, the country with the largest Muslim population, has made significant progress by establishing infrastructure such as Sharia banking, Zakat and Waqf institutions, and the Halal industry. In contrast, Cambodia, with its small Muslim population, is still in the early stages of developing its Islamic economy. However, the country shows growth potential through the support of its Muslim community and cooperation with foreign Islamic financial institutions. This study employs a qualitative approach with a descriptive-comparative method through literature reviews, observations, and interviews. The results show a significant gap in the implementation of Islamic economics between Indonesia and Cambodia. However, both countries have the opportunity to develop this system according to their social characteristics and national policies. This study concludes that, despite their different levels of development, Indonesia and Cambodia have the potential to strengthen the Islamic economic system through contextual and collaborative strategies. These findings are expected to bolster Islamic economic practices and inform policy formulation in both countries.   Keywords: Islamic Economics,Indonesia and Cambodia ,Shariah Finance,Comparative Study,Economic Development